PENGARUH RASIO LIKUIDITAS DAN LEVERAGE TERHADAP FINANCIAL DISTRESS DENGAN RASIO PROFITABILITAS SEBAGAI PEMODERASI - Selvia Eri Kuntari; Zaky Machmuddah (Dinamika Akuntansi Keuangan dan Perbankan, 2021)
Based on the data obtained, this study was made with the intention of analyzing and examining the liquidity andleverage variables in financial distress with the profitability ratio as moderating in manufacturing companies listed onthe IDX with 3 years of observation, namely the 2017-2019 period. The independent variable is proxied by usingCurrent Ratio (CR) as the liquidity variable and Debt to Equity Ratio (DER) as the leverage variable. The moderatingvariable is proxied using Return on Assets (ROA), while the variable using the Z-Score proxy (Altman). The populationis manufacturing companies for the period 2017-2019 and is listed on the IDX. The sample taken is 99 manufacturingcompanies with purposive sampling method. The method of analysis uses logistic regression. The results of the researchtested show that CR has an effect on financial distress. Meanwhile DER does not affect financial difficulties. However,it is different from ROA, ROA, the effect of CR and DER on financial distress.